Чисельність та правове становище київського міщанства в кінці XVIII – середині ХІХ ст. - Кохан, О. (Краєзнавство, 2016)
У статті з'ясовується чисельність київського міщанства в кінці XVIII – середині ХІХ ст.
Аналізуються зміни у правовому становищі київських міщан в умовах панування Російської
імперії. В статье устанавливается численность киевского мещанства в конце XVIII – середине
ХІХ вв. Анализируются изменения в правовом положении киевских мещан в условиях господства
Российской империи. At the beginning of the 19th century the whole people who lived in Kyiv were divided into three
categories: permanent, temporary and transition.
Burghers were the largest strata among all of the population in Kyiv. Before 1795 there were 3593
burghers in the city, in 1795 – 4900, in 1835 – 17440, in 1845 – 21851.
The legal status of the Kyiv burghers was determined by the legislation of those countries, which
Kyiv entered in different historical time. From the end of the 18th century Kyiv gradually began to
obey the Russian Empire.
According to the legislation of the Russian Empire, all the burghers belonged to the tributary class.
During the 19th century Kyiv burghers paid: state taxes, rural duties, taxes on food, paid for those
who prescribed in bourgeoisie, arrearages.
Also Kyiv burghers were prescribed in the city. It complicated the possibility of moving to another
city.
Except taxes burghers bear different duties. One of them was recruiting duty. Kyiv burghers were
free from the duty till 1835. The first set of recruits was held in Kyiv July 1, 1836, when there were
taken into military service 18 burghers.
Another duty was billeting, which was the hardest one. It was the duty to take in their homes officers
and soldiers from the military units. It meant not only to allocate rooms for them, but also to service
them, especially when there were officers nobility.